Lean Construction as an Efficiency Strategy for Sustainable Infrastructure: A Systematic Literature Review - Ximenes, Firmino Fitrino; Pramesti, Nectaria Putri (Civil and Sustainable Urban Engineering, 2025)
The construction industry continued to face major challenges related to inefficiency, resource waste, and significant environmental impacts. These issues highlighted the urgent need for more effective project management strategies to support sustainable infrastructure development. This study aimed to synthesize existing knowledge on the role of Lean Construction (LC) as an efficiency strategy in achieving sustainable infrastructure, while also identifying research gaps related to digital integration and the circular economy. A Systematic Literature Review (SLR) was conducted on 433 publications indexed in Scopus between 2015 and 2025. After applying inclusion and exclusion criteria as well as a quality assessment framework, 14 articles were selected for detailed analysis. The findings indicated that 71.4% of the reviewed studies emphasized LC integration with sustainability and digital technologies, particularly Building Information Modeling (BIM) and digital twins. Waste reduction (64.3%), cost efficiency (57.1%), time efficiency (50%), and implementation barriers (42.9%) also emerged as dominant themes. However, the integration of LC with Circular Economy (CE) principles, such as reuse, recycling, and design for deconstruction, remained limited. Furthermore, the social dimension of sustainability, including occupational safety, labor welfare, and collaborative culture, received minimal empirical attention. This study concluded that LC had significant potential to enhance project efficiency and sustainability, but its application was still predominantly conceptual, with limited validation in developing countries. Recommendations included expanding empirical field studies in the Global South, strengthening LC–BIM–CE integration in practice, developing practical tools and matrices to support implementation, and promoting regulatory frameworks that enable wider adoption.